The effectiveness of new urban trail infrastructure on physical activity and active transportation: a systematic review and meta-analysis of natural experiments - Isaak Fast; Christie Nashed; Jack Lotscher; Nicole Askin; Hannah Steiman De Visser; Jonathan McGavock (International Journal of Behavioral Nutrition and Physical Activity)
Abstract Background Cities in Western countries are investing billions of dollars in new cycling infrastructure (urban trails) to support active transportation (AT) and leisure-type physical activity (PA). Little empirical evidence exists on the effectiveness of urban trails on changes in AT or PA. Design and methods We searched CINAHL, OVID, SPORTDiscus, Transport Research International Documentation (TRID), Web of Science Core Collection and Google Scholar for articles published from 2010 to 2023. We included controlled experimental studies that reported PA, AT or trail counts as outcome measures before and after construction of an urban trail. A modified risk of bias tool was employed to assess the methodological quality of each selected study (Prospero ID: CRD42023438891). Results Three independent reviewers screened abstracts from 3936 articles identified in the original search and identified 24 articles that met inclusion criteria: 11 studies (n = 11,464) that measured changes in PA, 8 studies (n = 92,001) that measured changes in cycling traffic and 5 studies (n = 4,958,203) that measured changes in rates of AT/cycling. Meta-analysis revealed that new trails increased PA levels among individuals in proximity to one, compared to those living in control areas (SMD = 0.12; 95% CI: 0.04, 0.20; I2 = 73%; n = 11,464). This effect was marginally stronger when data were restricted to individuals living in closest proximity to trails (SMD = 0.14; 96% CI: 0.06 to 0.25, I2 = 74%; n = 8234). Meta-analyses were not possible for measures of AT and cycling counts. All studies were at high risk of bias due to a failure to adhere to reporting guidelines for quasi-experimental studies. Conclusions There is limited but intriguing evidence that the addition of protected urban trails increases daily PA for individuals living in neighbourhoods that receive them. The strength of this evidence could be enhanced with the application of and adherence to principles of causal inference and increased diversity of individuals included in study designs.